(untitled) (Balthazar, 2020)
Indignation, especially when it manifests itself as an emotional reaction to the injustice suffered by others, has been variably explained as a feeling generated by benevolence and closeness towards others or, on the contrary, by resentment and envy. If, in its positive meaning, indignation seems to be related to the possession of a strong sense of right or of a strong sense of respect for social norms, in its negative one - as for Nietzsche - it seems to present itself as a passion that stands on the line between sadism and masochism. Following Spinoza and the effort to preserve itself that, for the Dutch philosopher, everything possesses, it will be argued that indignation is a reaction to an unfulfilled desire for self-affirmation, and that it can be educated in order to make this individual and selfish impulse able to give rise to practices of collective transformation and liberation.